A nickel-based water electrolysis catalytic material and preparation method thereof
By using a nickel matrix and a microporous nickel layer as electrode materials in an alkaline water electrolytic cell, the problem of low catalytic activity of the nickel electrode is solved, the current density is improved and the hydrogen production efficiency is improved, while ensuring the stability and cost-effectiveness of the material.
Patent Information
- Application Number
- CN202411015062.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The catalytic activity of nickel electrodes in existing alkaline water electrolytic cells is low, resulting in low current density and low hydrogen production efficiency. The existing improved methods such as Rainey nickel electrodes and porous nano-nickel layers have problems of high cost and insufficient stability.
A nickel matrix and a microporous nickel layer attached thereto are prepared by spraying, high-temperature calcining and reduction treatment processes. The nickel matrix is a mesh structure, the average pore diameter of the microporous nickel layer is 0.15-0.5 μm and the loading capacity is 3-10 mg/cm2.
It improves the current density of alkaline water electrolytic cells, improves hydrogen production efficiency, and has good catalytic performance, long-term stability and low cost, and is suitable for large-scale commercial applications.
Smart Images

Figure CN118814199B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water electrolysis, and specifically relates to a nickel-based water electrolysis catalytic material and a preparation method thereof. Background Art
[0002] Currently, hydrogen production through water electrolysis using renewable energy has become a new development trend. Among them, alkaline water electrolysis hydrogen production technology has obvious advantages in single-tank large-scale and low equipment cost.
[0003] The alkaline water electrolyzer is mainly composed of a plurality of electrolytic chambers separated into cathode and anode by diaphragm materials. Hydrogen evolution reaction occurs at the cathode, and water molecules gain electrons and are reduced to hydrogen gas and hydroxide ions, i.e. 2H2O+2e - →H2+2OH - , the hydroxide ions pass through the diaphragm into the anode, lose electrons, undergo oxygen evolution reaction, and are oxidized into oxygen and water molecules, namely 2OH - →1 / 2O2+H2O+2e - , and the electrochemical reactions of hydrogen evolution and oxygen evolution both occur on the surface of the electrode material.
[0004] The anode electrode / cathode electrode is a key component in an alkaline water electrolyzer and is usually required to have excellent catalytic performance, good electrical conductivity, and stable physical and chemical properties to ensure that the water electrolysis reaction is efficient and stable.
[0005] Existing materials for industrial applications, such as precious metal catalysts, commercial nickel mesh, etc. Taking commercial nickel mesh as an example, the working current density of alkaline water electrolyzers using commercial nickel mesh is usually only 0.2A / cm 2 ~0.3A / cm 2 , which is mainly due to the low intrinsic catalytic activity of nickel electrodes.
[0006] The improvement of nickel electrode materials is mainly carried out through surface coating:
[0007] First, the Raney nickel electrode with relatively good catalytic performance is used. That is, the aluminum in the nickel-aluminum alloy is washed away by high-concentration alkali solution, and then the Raney nickel catalytic layer is prepared on the surface of the nickel mesh. This coating method not only consumes a large amount of non-precious metals, but also generally requires a loading of 20 to 25 mg / cm 2 , which will lead to an increase in the cost per unit area. In addition, the Raney nickel catalyst layer is not tightly bonded to the base nickel mesh material, and the Raney nickel catalyst layer is easy to fall off, resulting in insufficient long-term stability.
[0008] Secondly, the efficiency of water electrolysis is improved and energy consumption is reduced by loading a commercial nickel mesh with a porous nano-nickel layer. For example, patent CN113174600A provides a porous nickel mesh water electrolysis catalytic material and a preparation method thereof. The preparation method of the porous nickel mesh water electrolysis catalytic material comprises the following steps: (1) in a two-electrode system, an electrolyte is provided in an electrolytic cell, a pretreated commercial nickel mesh is used as a working electrode, a platinum sheet is used as a counter electrode, and after applying current, a nickel nanoparticle layer is loaded on the commercial nickel mesh using an electrodeposition method to obtain a commercial nickel mesh loaded with a nickel nanoparticle layer; (2) after the commercial nickel mesh loaded with the nickel nanoparticle layer in step (1) is taken out of the electrolytic cell, the porous nickel mesh water electrolysis catalytic material is obtained by washing and natural drying. Compared with the currently used commercial nickel mesh, the porous nickel mesh water electrolysis catalytic material prepared in this scheme has a higher catalytic activity, can effectively improve the efficiency of water electrolysis, reduce energy consumption, and thus significantly reduce the cost of hydrogen production by water electrolysis. However, the average pore size of the porous nano-nickel layer obtained by the electrodeposition method is generally between a dozen and several dozen microns, which has limited effect on improving the active surface area and current density.
[0009] Therefore, how to provide an electrode material for alkaline water electrolysis with good catalytic performance, suitable catalyst loading and long-term stability to improve the problem of low current density in the alkaline water electrolyzer and enhance hydrogen production efficiency is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0010] In view of the defects existing in the above-mentioned prior art, the present invention provides a nickel-based electrolytic water catalytic material and a preparation method thereof, wherein the nickel-based electrolytic water catalytic material comprises: a nickel substrate and a microporous nickel layer attached to the nickel substrate; wherein the nickel substrate is a mesh structure, the microporous nickel layer is attached to the mesh wire, the mesh wire diameter of the nickel substrate is not more than 0.25 mm, the average thickness of the microporous nickel layer is 10-40 μm, and the average pore size is 0.15-0.5 μm; after the ultrasonic test, the shedding proportion of the nickel-based electrolytic water catalytic material is not more than 5%. The present invention prepares the nickel-based electrolytic water catalytic material by the process of spraying, high-temperature calcination, and reduction treatment. The process is convenient and stable, and can realize large-scale and large-scale commercial applications. The nickel-based electrolytic water catalytic material has good catalytic performance, suitable catalyst loading and long-term stability. As an electrode material of an alkaline water electrolyzer, it improves the problem of low current density of the alkaline water electrolyzer and improves the hydrogen production efficiency.
[0011] In a first aspect, the present invention provides a nickel-based water electrolysis catalytic material, comprising: a nickel substrate and a microporous nickel layer attached to the nickel substrate;
[0012] The nickel matrix is a mesh structure, the microporous nickel layer is attached to the mesh wire, the wire diameter of the nickel matrix mesh wire is not greater than 0.25 mm, the average thickness of the microporous nickel layer is 10 to 40 μm, and the average pore diameter is 0.15 to 0.5 μm.
[0013] Furthermore, the loading of the microporous nickel layer on the nickel substrate is 3 to 10 mg / cm 2 .
[0014] Further, the thickness of the nickel substrate is 0.1 to 0.7 mm;
[0015] The relationship between the wire diameter of the nickel matrix mesh and the thickness and average pore diameter of the microporous nickel layer is as follows:
[0016]
[0017] Wherein, α is the active area reference specific gravity, P is the porosity of the microporous nickel layer, R is the wire diameter of the nickel matrix mesh, t is the thickness of the microporous nickel layer, and d is the average pore size of the microporous nickel layer.
[0018] Furthermore, the nickel-based water electrolysis catalytic material is used as the electrode of the alkaline water electrolyzer, and the current density at a voltage of 1.8V is not less than 0.35A / cm 2 .
[0019] In a second aspect, the present invention also provides a method for preparing the above-mentioned nickel-based water electrolysis catalytic material, which specifically comprises the following steps:
[0020] S1: preparing a raw material component of a water electrolysis catalytic material by coating a nickel oxide-containing catalyst slurry on a nickel substrate;
[0021] S2: subjecting the raw material components obtained in S1 to high-temperature sintering and reduction treatment to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer.
[0022] Furthermore, step S1 specifically includes the following steps:
[0023] S11: preparing a uniformly mixed nickel oxide-containing catalyst slurry;
[0024] S12: cutting, flattening, and cleaning the nickel mesh raw material to obtain a nickel matrix;
[0025] S13: coating the nickel oxide-containing catalyst slurry of S11 on the surface of the nickel substrate of S12 at a preset temperature of 90-120° C.;
[0026] S14: Drying to prepare the raw material components of the water electrolysis catalytic material.
[0027] Furthermore, step S11 specifically includes the following steps:
[0028] S111: Obtain nickel oxide powder raw material and put it into a specific container;
[0029] S112: adding a first solvent raw material into a specific container, and using an ultrasonic cleaning machine to uniformly mix the first solvent raw material with the nickel oxide powder raw material;
[0030] S113: adding a second solvent raw material into a specific container, and using an ultrasonic cleaning machine to uniformly mix the second solvent raw material with the mixture obtained in S112;
[0031] S114: adding a dispersant raw material into a specific container, and uniformly mixing the dispersant raw material with the mixture obtained in S113 by using an ultrasonic cleaning machine and an ultrasonic cell crusher;
[0032] S115: Stir the specific container at a rotation speed of not less than 600 rpm for not less than 12 hours to obtain a uniformly mixed catalyst slurry.
[0033] Furthermore, the first solvent raw material is isopropanol, the second solvent raw material is deionized water, and the dispersant raw material is a Nafion solution with a mass fraction of 5-20%;
[0034] The total mass fraction of the nickel oxide powder and the Nafion solid in the dispersant is 0.5 to 1.5%;
[0035] The mass ratio of nickel oxide powder to Nafion solid is (4-5):1, and the mass ratio of isopropanol to deionized water is (8-15):1.
[0036] Furthermore, step S2 specifically includes the following steps:
[0037] S21: placing the raw material components obtained in S1 in a tube furnace and calcining them at high temperature in a nitrogen atmosphere, wherein the calcination temperature is 800 to 1100° C. and the calcination time is 3 to 5 hours;
[0038] S22: After calcination, the atmosphere in the tubular furnace is switched to pure hydrogen and high-temperature calcination reduction is performed. After being taken out for cleaning and drying, the temperature of the high-temperature calcination reduction is 300-600°C, and the time of the high-temperature calcination reduction is 5.5-6.5h to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer.
[0039] Furthermore, the flow rates of nitrogen and hydrogen introduced into S21 and S22 are not less than 100 sccm.
[0040] The present invention provides a nickel-based water electrolysis catalytic material and a preparation method thereof, which at least have the following beneficial effects:
[0041] First, the nickel-based water electrolysis catalytic material provided by the present invention retains the inherent pore structure of the nickel matrix, which is beneficial to electrolyte collection and gas diffusion during alkaline water electrolysis, thereby maintaining a low mass transfer resistance.
[0042] Second, the nickel catalytic layer with a microporous structure attached to the nickel-based water electrolysis catalytic material can increase the surface area of the catalytic material itself and increase the active sites of the water electrolysis reaction, thereby reducing the area specific resistance.
[0043] Third, through the steps of spraying, high-temperature sintering and reduction treatment, the prepared microporous nickel catalyst layer is tightly bonded to the base nickel mesh material and is not easy to fall off. It has good high-temperature durability and can ensure the long-term stable operation of the alkaline water electrolyzer.
[0044] In addition, the nickel-based water electrolysis catalytic material provided by the present invention has a lower loading and better and more stable performance than existing non-precious metal catalysts. Compared with the common precious metal alkaline fuel cells on the market, the non-precious metal materials used in the nickel-based water electrolysis catalytic material have low cost and catalytic performance that meets large-scale and large-scale commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a surface SEM micrograph of the nickel-based water electrolysis catalytic material of Example 1 provided by the present invention. DETAILED DESCRIPTION
[0046] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0048] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0049] The present invention focuses on the modification research of nickel electrode materials. A nickel-based water electrolysis catalytic material is prepared by surface coating in the form of spraying, high-temperature calcination, and reduction treatment. The process is convenient and stable, and can be used in large-scale commercial applications. The nickel-based water electrolysis catalytic material has good catalytic performance, suitable catalyst loading and long-term stability. As an electrode material for an alkaline water electrolyzer, it improves the problem of low current density of the alkaline water electrolyzer and improves the hydrogen production efficiency.
[0050] In a first aspect, the present invention provides a nickel-based water electrolysis catalytic material, comprising: a nickel substrate and a microporous nickel layer attached to the nickel substrate;
[0051] The nickel matrix is a mesh structure, the microporous nickel layer is attached to the mesh wire, the wire diameter of the nickel matrix mesh wire is not greater than 0.25 mm, the average thickness of the microporous nickel layer is 10 to 40 μm, and the average pore diameter is 0.15 to 0.5 μm;
[0052] After the ultrasonic test, the shedding proportion of the nickel-based water electrolysis catalytic material is no more than 5%.
[0053] Furthermore, the loading of the microporous nickel layer on the nickel substrate is 3 to 10 mg / cm 2 .
[0054] Further, the thickness of the nickel substrate is 0.1 to 0.7 mm;
[0055] The relationship between the wire diameter of the nickel matrix mesh wire and the thickness and average pore diameter of the microporous nickel layer is as follows:
[0056]
[0057] Wherein, α is the active area-based specific gravity, P is the porosity of the microporous nickel layer, R is the wire diameter of the nickel matrix mesh, t is the thickness of the microporous nickel layer, and d is the average pore size of the microporous nickel layer.
[0058] The value of the active area base specific gravity α is determined according to different alkaline water electrolysis needs, and the porosity of the microporous nickel layer needs to be limited to the range of 25%-55%. The model selection of the nickel matrix mesh, the thickness of the coated sintered microporous nickel layer, and the average pore size must meet the above relationship. The nickel-based electrolytic water catalytic material prepared in this way can be used as an electrode material for an alkaline water electrolyzer to improve the problem of low current density in the alkaline water electrolyzer.
[0059] Furthermore, the nickel-based water electrolysis catalytic material is used as the electrode of the alkaline water electrolyzer, and the current density at a voltage of 1.8V is not less than 0.35A / cm 2 .
[0060] In a second aspect, the present invention also provides a method for preparing the above-mentioned nickel-based water electrolysis catalytic material, which specifically comprises the following steps:
[0061] S1: preparing a raw material component of a water electrolysis catalytic material by coating a nickel oxide-containing catalyst slurry on a nickel substrate;
[0062] S2: subjecting the raw material components obtained in S1 to high-temperature sintering and reduction treatment to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer.
[0063] Furthermore, step S1 specifically includes the following steps:
[0064] S11: preparing a uniformly mixed nickel oxide-containing catalyst slurry;
[0065] S12: cutting, flattening, and cleaning the nickel mesh raw material to obtain a nickel matrix;
[0066] S13: coating the nickel oxide-containing catalyst slurry of S11 on the surface of the nickel substrate of S12 at a preset temperature of 90-120° C.;
[0067] S14: Drying to prepare the raw material components of the water electrolysis catalytic material.
[0068] Furthermore, step S11 specifically includes the following steps:
[0069] S111: Obtain nickel oxide powder raw material and put it into a specific container;
[0070] S112: adding a first solvent raw material into a specific container, and using an ultrasonic cleaning machine to uniformly mix the first solvent raw material with the nickel oxide powder raw material;
[0071] S113: adding a second solvent raw material into a specific container, and using an ultrasonic cleaning machine to uniformly mix the second solvent raw material with the mixture obtained in S112;
[0072] S114: adding a dispersant raw material into a specific container, and uniformly mixing the dispersant raw material with the mixture obtained in S113 by using an ultrasonic cleaning machine and an ultrasonic cell crusher;
[0073] S115: Stir the specific container at a rotation speed of not less than 600 rpm for not less than 12 hours to obtain a uniformly mixed catalyst slurry.
[0074] Furthermore, the first solvent raw material is isopropanol, the second solvent raw material is deionized water, and the dispersant raw material is a Nafion solution with a mass fraction of 5-20%;
[0075] The total mass fraction of the nickel oxide powder and the Nafion solid in the dispersant is 0.5 to 1.5%;
[0076] The mass ratio of nickel oxide powder to Nafion solid is (4-5):1, and the mass ratio of isopropanol to deionized water is (8-15):1.
[0077] The Nafion solution used in the present invention is a perfluorosulfonic acid resin dissolved in a mixed solvent of water and n-propanol, wherein the content of Nafion solid (i.e., solute, perfluorosulfonic acid resin) is 5-5.4wt.%, the content of water in the solvent of the Nafion solution is 42-48wt.%, and the content of n-propanol is 47-53wt.%. In addition, the total acidity of the Nafion solution is 1.03-1.12meq / g.
[0078] Furthermore, step S2 specifically includes the following steps:
[0079] S21: placing the raw material components obtained in S1 in a tube furnace and calcining them at high temperature in a nitrogen atmosphere, wherein the calcination temperature is 800 to 1100° C. and the calcination time is 3 to 5 hours;
[0080] S22: After calcination, the atmosphere in the tubular furnace is switched to pure hydrogen and high-temperature calcination reduction is performed. After being taken out for cleaning and drying, the temperature of the high-temperature calcination reduction is 300-600°C, and the time of the high-temperature calcination reduction is 5.5-6.5h to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer.
[0081] Furthermore, the flow rates of nitrogen and hydrogen introduced into S21 and S22 are not less than 100 sccm.
[0082] Embodiment 1:
[0083] Example 1: A nickel-based water electrolysis catalytic material was prepared.
[0084] In Example 1, the specific preparation process is as follows:
[0085] S1: obtaining a raw material component coated with a nickel oxide-containing catalyst slurry.
[0086] The nickel oxide catalyst slurry is prepared according to a solid content of 1%, nickel oxide powder is weighed and added to a silk-mouth reagent bottle, isopropanol is measured with a measuring cylinder and added to the silk-mouth reagent bottle, the bottle is tightly covered with a lid and placed in an ultrasonic cleaner for 5 minutes to mix evenly; deionized water is pipetted with a pipette and added to the silk-mouth reagent bottle, the bottle is tightly covered with a lid and placed in an ultrasonic cleaner for 5 minutes to mix evenly; Nafion solution is pipetted with a pipette and added to the silk-mouth reagent bottle, the bottle is tightly covered with a lid and placed in an ultrasonic cleaner for 10 minutes to mix evenly; the mixed reagent bottle is placed in an ultrasonic cell crusher and crushed and dispersed for 20 minutes to disperse evenly; a magnet is added to the dispersed reagent bottle, the bottle is tightly covered with a lid and stirred at a speed of 600 rpm on a magnetic stirrer for 12 hours to obtain a nickel oxide catalyst slurry.
[0087] The nickel mesh raw material is cut, flattened, and ultrasonically cleaned to obtain a nickel substrate with a smooth and clean surface: a woven nickel mesh with 60 mesh and a wire diameter of 0.25 mm is selected as the nickel mesh raw material, and is cut into 2.5 cm×2.5 cm squares using a laser cutting machine; the cut nickel mesh is clamped with two stainless steel metal blocks with smooth and flat surfaces, and is placed in a manual tablet press, the pressure is set to 10 MPa, and the pressure is maintained for 150 s. After the pressure is released, the nickel mesh is taken out to obtain a nickel mesh with a flat surface and unaffected overall thickness; the flattened nickel mesh is placed in beakers containing 100 ml of propanol, deionized water, and ethanol, respectively, and placed in an ultrasonic cleaner for ultrasonic cleaning, and the cleaned nickel mesh is dried to obtain a clean and smooth nickel substrate.
[0088] The nickel oxide-containing catalyst slurry is ultrasonically sprayed onto the surface of the nickel substrate, followed by drying to prepare a catalyst coated with nickel oxide:
[0089] The prepared 1% solid content nickel oxide catalyst slurry is sucked into the feed syringe of the ultrasonic sprayer, the bottom plate heating is set to make the surface temperature of the nickel substrate 90°C, the number of spraying circles is set to 300 circles, and the nickel oxide catalyst slurry is evenly sprayed onto the surface of the nickel substrate.
[0090] S2: The raw material parts coated with the nickel oxide catalyst slurry are subjected to high-temperature sintering and reduction treatment to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer.
[0091] The prepared raw material component coated with the nickel oxide catalyst slurry was placed in a tubular furnace, nitrogen at a flow rate of 100 sccm was introduced into the tubular furnace, and the temperature was raised to 1000°C for high-temperature calcination for 4 hours to remove the dispersant (i.e., Nafion) in the nickel oxide catalyst slurry so that the nickel oxide solid is tightly combined with the nickel matrix.
[0092] After calcination, the nitrogen in the tube furnace was switched to hydrogen with a flow rate of 100 sccm, and the nickel oxide was reduced at a high temperature of 500°C for 6 hours to reduce the nickel oxide to a single nickel substance and form a microporous structure. After being taken out for cleaning and drying, a nickel-based electrolytic water catalytic material with a microporous nickel layer attached to the surface of the nickel substrate was obtained. The morphology of the microstructure is as follows: Figure 1 shown.
[0093] The nickel-based water electrolysis catalytic material prepared in this embodiment includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 22 μm, the average pore size is 0.3 μm, and the loading of the microporous nickel layer is 6.9 mg / cm 2 .
[0094] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this embodiment is 2.39%. The nickel-based water electrolysis catalytic material prepared in this embodiment is used as an electrode of an alkaline water electrolyzer. The current density at a voltage of 1.8 V is 0.423 A / cm 2 .
[0095] Embodiment 2:
[0096] Example 2: Nickel-based water electrolysis catalytic material was prepared.
[0097] In Example 2, relative to the preparation process of Example 1, the following parameters were adjusted:
[0098] The prepared 1% solid content nickel oxide catalyst slurry is sucked into the feed syringe of the ultrasonic sprayer, the bottom plate heating is set to make the surface temperature of the nickel substrate 90°C, the number of spraying circles is set to 200 circles, and the nickel oxide catalyst slurry is evenly sprayed onto the surface of the nickel substrate.
[0099] The nickel-based water electrolysis catalytic material prepared in this embodiment includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 15 μm, the average pore size is 0.3 μm, and the loading of the microporous nickel layer is 4.6 mg / cm 2 .
[0100] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this embodiment is 2.08%. The nickel-based water electrolysis catalytic material prepared in this embodiment is used as an electrode of an alkaline water electrolyzer. The current density at a voltage of 1.8 V is 0.358 A / cm 2 .
[0101] Embodiment 3:
[0102] Example 3: Nickel-based water electrolysis catalytic material was prepared.
[0103] In Example 3, relative to the preparation process of Example 1, the following parameters were adjusted:
[0104] The nickel mesh raw material is cut, flattened, and ultrasonically cleaned to obtain a nickel substrate with a smooth and clean surface: a woven nickel mesh with 100 mesh and a wire diameter of 0.15 mm is selected as the nickel mesh raw material, and is cut into 2.5 cm×2.5 cm squares using a laser cutting machine; the cut nickel mesh is clamped with two stainless steel metal blocks with smooth and flat surfaces, and is placed in a manual tablet press, the pressure is set to 6 MPa, and the pressure is maintained for 120 s. After the pressure is released, the nickel mesh is taken out to obtain a nickel mesh with a flat surface and unaffected overall thickness; the flattened nickel mesh is placed in beakers containing 100 ml of propanol, deionized water, and ethanol, respectively, and placed in an ultrasonic cleaner for ultrasonic cleaning, and the cleaned nickel mesh is dried to obtain a clean and smooth nickel substrate.
[0105] The nickel-based water electrolysis catalytic material prepared in this embodiment includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.32 mm, the average thickness of the microporous nickel layer is 22 μm, the average pore size is 0.3 μm, and the loading of the microporous nickel layer is 6.9 mg / cm 2 .
[0106] The shedding ratio of the nickel-based water electrolysis catalytic material in this embodiment is 3.71%. The nickel-based water electrolysis catalytic material prepared in this embodiment is used as an electrode of an alkaline water electrolyzer. The current density at a voltage of 1.8 V is 0.376 A / cm 2 .
[0107] Embodiment 4:
[0108] Example 4: Nickel-based water electrolysis catalytic material was prepared.
[0109] In Example 4, relative to the preparation process of Example 1, the following parameters were adjusted:
[0110] After calcination, the nitrogen in the tube furnace was switched to hydrogen with a flow rate of 100 sccm, and the nickel oxide was reduced at a high temperature of 400°C for 6 hours to reduce the nickel oxide to a single nickel substance and form a microporous structure. After being taken out for cleaning and drying, a nickel-based water electrolysis catalytic material with a microporous nickel layer attached to the surface of the nickel substrate was obtained.
[0111] The nickel-based water electrolysis catalytic material prepared in this embodiment includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 21 μm, the average pore size is 0.2 μm, and the loading of the microporous nickel layer is 6.9 mg / cm 2 .
[0112] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this embodiment is 4.59%. The nickel-based water electrolysis catalytic material prepared in this embodiment is used as an electrode of an alkaline water electrolyzer. The current density at a voltage of 1.8 V is 0.383 A / cm 2 .
[0113] Comparative Example 1:
[0114] Comparative Example 1 prepared a nickel-based water electrolysis catalytic material.
[0115] In Comparative Example 1, relative to the preparation process of Example 1, the following parameters were adjusted:
[0116] S1: obtaining a raw material component coated with a nickel-containing elemental catalyst slurry.
[0117] According to the solid content of nickel-containing single substance catalyst slurry of 1%, pure nickel powder is weighed and added to a silk-mouth reagent bottle, isopropanol is measured with a measuring cylinder and added to the silk-mouth reagent bottle, the bottle is tightly covered with a lid and placed in an ultrasonic cleaner for ultrasonication for 5 minutes to mix it evenly; deionized water is pipetted with a pipette and added to the silk-mouth reagent bottle, the bottle is tightly covered with a lid and placed in an ultrasonic cleaner for ultrasonication for 5 minutes to mix it evenly; Nafion solution is pipetted with a pipette and added to the silk-mouth reagent bottle, the bottle is tightly covered with a lid and placed in an ultrasonic cleaner for ultrasonication for 10 minutes to mix it evenly; the mixed reagent bottle is placed in an ultrasonic cell crusher and crushed and dispersed for 20 minutes to disperse it evenly; a magnet is added to the dispersed reagent bottle, the bottle is tightly covered with a lid and stirred on a magnetic stirrer at a speed of 600 rpm for 12 hours to obtain a nickel-containing single substance catalyst slurry.
[0118] S2: The raw material parts coated with the nickel-containing elemental catalyst slurry are subjected to high-temperature sintering to obtain a nickel-based water electrolysis catalytic material with an attached nickel layer.
[0119] The prepared raw material parts coated with nickel-containing elemental catalyst slurry are placed in a tubular furnace, nitrogen at a flow rate of 100 sccm is introduced into the tubular furnace, and the temperature is raised to 1000°C for high-temperature calcination for 4 hours to remove the dispersant (i.e., Nafion) in the nickel-containing elemental catalyst slurry so that the nickel solid is tightly combined with the nickel matrix.
[0120] In this comparative example, pure nickel powder is used as the catalytic slurry, and the reduction treatment step is omitted in the treatment of the raw material parts, and only high-temperature sintering is performed.
[0121] The nickel-based water electrolysis catalytic material prepared in this comparative example includes: a nickel substrate with a mesh structure, and a nickel layer attached to the nickel substrate. The nickel layer is relatively dense and does not have a microporous structure.
[0122] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this comparative example is 4.58%. The nickel-based water electrolysis catalytic material prepared in this comparative example is used as an electrode of an alkaline water electrolyzer, and the current density at a voltage of 1.8 V is 0.156 A / cm 2 .
[0123] Comparative Example 2:
[0124] Comparative Example 2 prepared a nickel-based water electrolysis catalytic material.
[0125] In Comparative Example 2, relative to the preparation process of Example 1, the following parameters were adjusted:
[0126] After calcination, the nitrogen in the tube furnace was switched to hydrogen with a flow rate of 100 sccm, and the calcination reduction was carried out at a high temperature of 200°C for 6 hours to reduce part of the nickel oxide to nickel element and form a microporous structure. After being taken out for cleaning and drying, a nickel-based water electrolysis catalytic material with a microporous nickel layer attached to the surface of the nickel substrate was obtained.
[0127] The nickel-based water electrolysis catalytic material prepared in this comparative example includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 21 μm, and the average pore size is 0.07 μm.
[0128] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this comparative example is 9.69%. The nickel-based water electrolysis catalytic material prepared in this comparative example is used as an electrode of an alkaline water electrolyzer, and the current density at a voltage of 1.8 V is 0.195 A / cm 2 .
[0129] Comparative Example 3:
[0130] Comparative Example 3 prepared a nickel-based water electrolysis catalytic material.
[0131] In Comparative Example 3, relative to the preparation process of Example 1, the following parameters were adjusted:
[0132] The prepared 1% solid content nickel oxide catalyst slurry was sucked into the feed syringe of the ultrasonic sprayer, the bottom plate heating was set to make the surface temperature of the nickel substrate 90°C, the number of spraying circles was set to 800 circles, and the nickel oxide catalyst slurry was evenly sprayed onto the surface of the nickel substrate.
[0133] The nickel-based water electrolysis catalytic material prepared in this comparative example includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 55 μm, the average pore size is 0.3 μm, and the loading of the microporous nickel layer is 19.6 mg / cm 2 .
[0134] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this comparative example is 8.04%. The nickel-based water electrolysis catalytic material prepared in this comparative example is used as an electrode of an alkaline water electrolyzer, and the current density at a voltage of 1.8 V is 0.328 A / cm 2 .
[0135] Comparative Example 4:
[0136] Comparative Example 4 prepared a nickel-based water electrolysis catalytic material.
[0137] In Comparative Example 4, relative to the preparation process of Example 1, the following parameters were adjusted:
[0138] After calcination, the nitrogen in the tube furnace was switched to hydrogen with a flow rate of 100 sccm, and the calcination reduction was carried out at a high temperature of 500°C for 2 hours to reduce part of the nickel oxide to nickel element and form a microporous structure. After being taken out for cleaning and drying, a nickel-based water electrolysis catalytic material with a microporous nickel layer attached to the surface of the nickel substrate was obtained.
[0139] The nickel-based water electrolysis catalytic material prepared in this comparative example includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 21 μm, and the average pore size is 0.1 μm.
[0140] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this comparative example is 5.47%. The nickel-based water electrolysis catalytic material prepared in this comparative example is used as an electrode of an alkaline water electrolyzer, and the current density at a voltage of 1.8 V is 0.212 A / cm 2 .
[0141] Comparative Example 5:
[0142] Comparative Example 5 prepared a nickel-based water electrolysis catalytic material.
[0143] In Comparative Example 5, relative to the preparation process of Example 1, the following parameters were adjusted:
[0144] S2: The raw material parts coated with the nickel oxide catalyst slurry are subjected to high-temperature sintering and reduction treatment to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer.
[0145] The prepared raw material component coated with the nickel oxide catalyst slurry was placed in a tubular furnace, nitrogen at a flow rate of 100 sccm was introduced into the tubular furnace, and the temperature was raised to 700°C for high-temperature calcination for 4 hours to remove the dispersant (i.e., Nafion) in the nickel oxide catalyst slurry so that the nickel oxide solid is tightly combined with the nickel matrix.
[0146] The reduction treatment in this comparative example is consistent with the reduction treatment process of Example 1. The nickel-based water electrolysis catalytic material prepared in this comparative example includes: a nickel substrate with a mesh structure, and a microporous nickel layer attached to the nickel substrate. The thickness of the nickel substrate is 0.55 mm, the average thickness of the microporous nickel layer is 22 μm, the average pore size is 0.3 μm, and the loading of the microporous nickel layer is 6.9 mg / cm 2 .
[0147] The shedding specific gravity of the nickel-based water electrolysis catalytic material in this comparative example is 36.89%. The nickel-based water electrolysis catalytic material prepared in this comparative example is used as an electrode of an alkaline water electrolyzer, and the current density at a voltage of 1.8 V is 0.296 A / cm 2 .
[0148] Performance Test:
[0149] The catalytic materials prepared in Examples 1-4 and Comparative Examples 1-5 were used to prepare electrode materials for alkaline water electrolyzers, and IV (current density-voltage) curve tests were performed for electrochemical characterization of water electrolyzers. In addition, the performance data of the degree of bonding between the catalytic material coating and the substrate were also given through a shedding test.
[0150] The test conditions are as follows: the operating temperature of the electrolytic cell is 80°C, the pressure is normal pressure, the electrolyte used is 30% mass fraction KOH solution, the diaphragm used is Toray's third-generation PPS diaphragm, and accordingly, the voltage change response signal is collected, and the IV (current density-voltage) curve graph is tested respectively to obtain the current density when the voltage is 1.8V.
[0151] The shedding conditions are as follows: the sample size is 2.5 cm × 2.5 cm, weighed, and then placed in a beaker containing 50 ml of anhydrous ethanol and 50 ml of ultrapure water, and the beaker is placed in an ultrasonic cleaning machine with a power of 100 W, and the ultrasonic operation is performed for 15 minutes. After the operation, each sample is taken out, dried and weighed, and the weight difference before and after the ultrasonic operation is calculated. The ratio of the weight difference to the original weight is used as the shedding ratio (%), and the data of the current density and the shedding ratio are summarized in the following Table 1.
[0152] Table 1 Performance test data of various embodiments and comparative examples
[0153]
[0154]
[0155] From the test results in Table 1, we can see that:
[0156] Regarding the most important parameter of the alkaline water electrolyzer, current density, the alkaline water electrolyzer using the nickel-based water electrolysis catalytic materials of Examples 1-4 as electrode materials had a current density higher than 0.3 A / cm at a voltage of 1.8 V. 2 .
[0157] The test results of Example 1 show that the current density at a voltage of 1.8 V exceeds 0.4 A / cm 2 The current density at a voltage of 2.0V reaches 1.205A / cm2, far exceeding the commercial electrodes commonly used in industry.
[0158] The current density of the alkaline water electrolyzer using the catalytic materials prepared in Comparative Examples 1-2 as electrodes at a voltage of 1.8 V was lower than 0.2 A / cm 2 The current density of the alkaline water electrolyzer with the catalytic material prepared in Comparative Example 3 as an electrode at a voltage of 1.8V is close to that of each embodiment. However, the thickness of the microporous nickel layer of the catalytic material given in Comparative Example 3 is too large, and the shedding specific gravity is also large. With the extension of service time, the performance of the material will be significantly degraded. In addition, the catalytic materials prepared in Comparative Examples 4-5 are not sufficiently calcined or reduced. The current density of the alkaline water electrolyzer as an electrode at a voltage of 1.8V is less than 0.3A / cm 2 .
[0159] The nickel-based water electrolysis catalytic material provided by the present invention has excellent catalytic performance and long-term stability, mainly due to the following reasons:
[0160] First, the nickel-based water electrolysis catalytic material provided by the present invention retains the inherent pore structure of the nickel matrix, which is beneficial to electrolyte collection and gas diffusion during alkaline water electrolysis, thereby maintaining a low mass transfer resistance.
[0161] Second, the nickel catalytic layer with a microporous structure attached to the nickel-based water electrolysis catalytic material can increase the surface area of the catalytic material itself and increase the active sites of the water electrolysis reaction, thereby reducing the area specific resistance.
[0162] Third, through the steps of spraying, high-temperature sintering and reduction treatment, the prepared microporous nickel catalyst layer is tightly bonded to the base nickel mesh material and is not easy to fall off. It has good high-temperature durability and can ensure the long-term stable operation of the alkaline water electrolyzer.
[0163] In addition, the nickel-based water electrolysis catalytic material provided by the present invention has a lower loading and better and more stable performance than existing non-precious metal catalysts. Compared with the common precious metal alkaline fuel cells on the market, the non-precious metal materials used in the nickel-based water electrolysis catalytic material have low cost and catalytic performance that meets large-scale and large-scale commercial applications.
[0164] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a nickel-based water electrolysis catalytic material, characterized in that: The nickel-based water electrolysis catalytic material comprises: a nickel substrate and a microporous nickel layer attached to the nickel substrate; The nickel matrix is a mesh structure with a thickness of 0.1 to 0.7 mm. The microporous nickel layer is attached to the mesh wire. The wire diameter of the nickel matrix mesh wire is not more than 0.25 mm. The average thickness of the microporous nickel layer is 10 to 40 μm, the average pore diameter is 0.15 to 0.5 μm, and the loading of the microporous nickel layer is 3 to 10 mg / cm 2 ; The method specifically comprises the following steps: S1: A raw material component of a water electrolysis catalytic material is prepared by coating a nickel oxide catalyst slurry on a nickel substrate, wherein the preparation of the nickel oxide catalyst slurry specifically includes: S111 obtaining a nickel oxide powder raw material and placing it in a specific container; S112 adding a first solvent raw material into the specific container, and using an ultrasonic cleaning machine to evenly mix it with the nickel oxide powder raw material; S113 adding a second solvent raw material into the specific container, and using an ultrasonic cleaning machine to evenly mix it with the mixture obtained in S112; S114 adding a dispersant raw material into the specific container, and using an ultrasonic cleaning machine, Ultrasonic cell crusher is used to mix the mixture obtained in S113 uniformly; S115 stirs the specific container at a speed of not less than 600 revolutions per minute for not less than 12 hours to obtain a uniformly mixed catalyst slurry; the first solvent raw material is isopropanol, the second solvent raw material is deionized water, and the dispersant raw material is a Nafion solution with a mass fraction of 5-20%; the total mass fraction of the nickel oxide powder and the Nafion solid in the dispersant is 0.5-1.5%; the mass ratio of the nickel oxide powder to the Nafion solid is (4-5):1, and the mass ratio of isopropanol to deionized water is (8-15):1; S2: The raw material parts obtained in S1 are subjected to high-temperature sintering and reduction treatment to obtain a nickel-based water electrolysis catalytic material with an attached microporous nickel layer, wherein the high-temperature sintering temperature is 800-1100°C, the sintering time is 3-5h, the reduction temperature is 300-600°C, and the reduction time is 5.5-6.5h.
2. The method for preparing a nickel-based water electrolysis catalytic material according to claim 1, characterized in that: The relationship between the wire diameter of the nickel matrix mesh wire and the thickness and average pore diameter of the microporous nickel layer is as follows: Wherein, α is the active area-based specific gravity, P is the porosity of the microporous nickel layer, R is the wire diameter of the nickel matrix mesh, t is the thickness of the microporous nickel layer, and d is the average pore size of the microporous nickel layer.
3. The method for preparing a nickel-based water electrolysis catalytic material according to claim 1 or 2, characterized in that: The current density of the alkaline water electrolyzer using nickel-based water electrolysis catalytic materials as electrodes at a voltage of 1.8V is not less than 0.35A / cm 2 .
4. The method for preparing a nickel-based water electrolysis catalytic material according to claim 1, characterized in that: Step S1 specifically includes the following steps: S11: preparing a uniformly mixed nickel oxide-containing catalyst slurry; S12: cutting, flattening, and cleaning the nickel mesh raw material to obtain a nickel matrix; S13: coating the nickel oxide-containing catalyst slurry of S11 on the surface of the nickel substrate of S12 at a preset temperature of 90-120° C.; S14: Drying to prepare the raw material components of the water electrolysis catalytic material.
5. The method for preparing a nickel-based water electrolysis catalytic material according to claim 1, characterized in that: Step S2 specifically includes the following steps: S21: placing the raw material components obtained in S1 in a tube furnace and calcining them at high temperature under a nitrogen atmosphere; S22: After calcination, the atmosphere in the tubular furnace is switched to pure hydrogen and high-temperature calcination reduction is performed. The material is taken out for cleaning and drying to obtain a nickel-based water electrolysis catalytic material with a microporous nickel layer attached.
6. The method for preparing a nickel-based water electrolysis catalytic material according to claim 5, characterized in that: The flow rates of nitrogen and hydrogen introduced into S21 and S22 are not less than 100 sccm.
Citation Information
Patent Citations
Porous nickel net water electrolysis catalysis material and preparation method thereof
CN113174600A
Preparation method of sintered porous nickel-based catalytic electrode
CN117626320A